2014
DOI: 10.3892/or.2014.3428
|View full text |Cite
|
Sign up to set email alerts
|

EPO gene expression induces the proliferation, migration and invasion of bladder cancer cells through the p21WAF1-mediated ERK1/2/NF-κB/MMP-9 pathway

Abstract: Erythropoietin (EPO) is a cytokine that modulates the production of red blood cells. Previous studies have contradicted the assumed role of EPO in tumor cell proliferation. In the present study, we investigated the effect of EPO in the proliferation, migration and invasion that is involved in the signaling pathways and cell-cycle regulation of bladder cancer 5637 cells. The results showed that an overexpression of the EPO gene has a potent stimulatory effect on DNA synthesis, migration and invasion. EPO gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
(65 reference statements)
3
6
0
Order By: Relevance
“…Comparisons were made to unstimulated cells. Ã P < 0.05. cells [Park et al, 2014[Park et al, , 2015. Our findings support our proposal that EPO induces an EMT process in MCF10A cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Comparisons were made to unstimulated cells. Ã P < 0.05. cells [Park et al, 2014[Park et al, , 2015. Our findings support our proposal that EPO induces an EMT process in MCF10A cells.…”
Section: Discussionsupporting
confidence: 91%
“…We propose that EPO induces an increase of vimentin and Snail2 expression through a NFκB‐dependent pathway. Supporting our proposal, it has been demonstrated that EPO gene expression induces migration and invasion through MMP‐9 expression and NFκB activation in vascular smooth muscle cells and bladder cancer cells [Park et al, , ]. Our findings support our proposal that EPO induces an EMT process in MCF10A cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 9 The inhibitory effects of U0126 on MEK and ERK activation have been confirmed repeatedly, and treatments with U0126 have been shown to inhibit proliferation and migration of cancer cells in vivo and in vitro. 10 − 12…”
mentioning
confidence: 99%
“…Recently Ma et al (10) illustrated that SUMO-specific protease 1 regulates the proliferation and invasion of pancreatic cancer cells through MMP-9. Park et al (11) Mangiferin, also named as mango element or chinonin, is a natural polyphenolic compound extracted from the liliaceous plant, Anemarrhena. Modern pharmacological and clinical studies have shown that mangiferin has physiological activity and pharmacological effects in many aspects (12).…”
Section: Introductionmentioning
confidence: 99%